THE ROLE OF FIRM SIZE AND INDUSTRY SENSITIVITY AS MODERATION IN THE RELATIONSHIP BETWEEN SUSTAINABILITY AND FIRM PERFORMANCE: EVIDENCE FROM INDONESIA - Wahidatul Husnaini; Susi Retna Cahyaningtyas; Rahmi Sri Ramadhani; Baiq Elly Martiana (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The study investigates how firm size and industry sensitivity as moderators influence the relationship between sustainability and firm performance. Using a fixed effects Moderate Regression Analysis (MRA) on 1,406 firm-year observations of non-financial Indonesian public companies listed on the Indonesia Stock Exchange, that disclose sustainability information in their annual reports for the period 2010-2023, the study concludes that sustainability has a significant and positive impact on a firm's performance. However, firm size cannot moderate the relationship between sustainability and firm performance. Industry sensitivity has weaknesses in the relationship between sustainability and firm performance, which means firms are required to disclose more sustainability information due to higher risks. However, such disclosures often have a high cost and a negative impact on performance. The study supports legitimacy theory and advises regulators (like Indonesia's OJK) to implement sustainability disclosure rules gradually to avoid imposing excessive costs on firms in high-risk industries